Hygiene and Sanitation Campaign for COVID-19 Prevention in Tatah Belayung Banjarmasin Selatan - Hanny Maria Caesarina (UMBanjarmasin, 2021)
Since the end of 2019, the transmission of COVID-19 or Corona virus disease has been declared as a global pandemy in the world. Hygiene and sanitation became crucial as it needs to be a commont habit for everyone. Banjarmasin Selatan is one of a district in Banjarmasin where all the inhabitants are farmers, public laborer, and housewives. During observation, it can be seen that they still had lack of concern for Covid-10 prevention, especially for washing hands. Therefore, this community service was aimed to give a hygiene and sanitation campaign for COVID-19 prevention in Banjarmasin Selatan. The target was the local community of Tatah Belayung Banjarmasin Selatan. The method used was through online campaign via youtube channel video and offline campaign through a community event about the importance of hygiene and sanitation. The event also taught about how to make a simple hand sanitizer with natural ingredients and how to use it. The outcome of this community service were the local community can produce and make their own hand sanitation for COVID-19 prevention. They were ready to commit more to increase their awareness for hygiene and sanitation everyday.